2009
DOI: 10.1007/s00122-009-1115-1
|View full text |Cite
|
Sign up to set email alerts
|

Wide variability in kernel composition, seed characteristics, and zein profiles among diverse maize inbreds, landraces, and teosinte

Abstract: All crop species have been domesticated from their wild relatives, and geneticists are just now beginning to understand the consequences of artificial (human) selection on agronomic traits that are relevant today. The primary consequence is a basal loss of diversity across the genome, and an additional reduction in diversity for genes underlying traits targeted by selection. An understanding of attributes of the wild relatives may provide insight into target traits and valuable allelic variants for modern agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
132
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 45 publications
7
132
0
1
Order By: Relevance
“…The protein and oil contents of the southwestern maize accessions, except Flor del Rio, were higher than those of Ohio Blue. Flint-Garcia et al (2009) showed that many maize landraces were higher in protein and oil than modern inbreds. Protein and oil values of landraces thus would appear to be higher than those reported for Corn Belt hybrids in multiple studies (Watson, 2003;Belyea et al, 2004;Dudley et al, 2007;Jaradat and Goldstein, 2013) and quality protein maize hybrids (Zarkadas et al, 2000).…”
Section: Accessionmentioning
confidence: 99%
“…The protein and oil contents of the southwestern maize accessions, except Flor del Rio, were higher than those of Ohio Blue. Flint-Garcia et al (2009) showed that many maize landraces were higher in protein and oil than modern inbreds. Protein and oil values of landraces thus would appear to be higher than those reported for Corn Belt hybrids in multiple studies (Watson, 2003;Belyea et al, 2004;Dudley et al, 2007;Jaradat and Goldstein, 2013) and quality protein maize hybrids (Zarkadas et al, 2000).…”
Section: Accessionmentioning
confidence: 99%
“…parviglumis ) in southern Mexico ∼7500–9000 years ago (Matsuoka et al 2002; Piperno et al 2009; Hufford et al 2012) but bears striking morphological differences in terms of plant, inflorescence, and seed architecture (Doebley et al 1995). Today, maize breeders and geneticists are well aware of the reduction in genetic diversity during crop domestication, especially in genes underlying traits that were targeted by the selection process (Flint-Garcia 2013), which resulted in lower or no variation in traits and limited the discovery of novel alleles that have potential to improve a crop’s germplasm (Flint-Garcia et al 2009). …”
mentioning
confidence: 99%
“…Similarly, kernel composition differs between teosinte and modern maize; on a dry matter basis (DMB), inbred maize kernels are ∼71.7% starch, ∼9.5% protein, and ∼4.3% oil (Watson et al 2003). In contrast, teosinte kernels have ∼52.92% starch, ∼28.71% protein, and ∼5.61% oil, strongly suggesting that the increase in kernel size, fruitcase-less kernels, and increase in kernel starch were the targets of artificial selection during maize domestication (Flint-Garcia et al 2009). …”
mentioning
confidence: 99%
“…Maize seeds contain ~10% proteins and ~70% of them are classified as storage proteins. Based on their solubility in different solvents, endosperm proteins are divided into four groups: albumins, globulins, glutelines, and prolamins (Flint-Garcia et al, 2009;Wu and Messing, 2014). Genetic purity and verity identification of maize can be carried out effectively through sodium dodecyl sulphate polyacrylamide gel electrophoresis -SDS-PAGE (Khan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%